Tinjauan Hukum Pidana Islam terhadap Tindak Pidana Pencurian dalam Putusan Pengadilan Negeri Pasaman Barat Nomor 150/PID.B/2021/PN PSB - Afrila, Nora; Basir, Gusril; Bustamar, Bustamar; Ridha, Muhammad (Lembaga Yasin AlSys, 2026)
The criminal act of livestock theft is one form of crime that causes unrest and losses for rural communities because livestock has high economic value and serves as a primary source of livelihood. In Indonesian positive law, livestock theft committed jointly is regulated under Article 363 paragraph (1) of the Criminal Code, whereas in Islamic criminal law theft is included as a jarimah that is, in principle, punishable by hudud sanctions if certain conditions are fulfilled. This study aims to examine a court decision concerning the criminal act of livestock theft from the perspective of Islamic criminal law, particularly the Decision of the Pasaman Barat District Court Number 150/Pid.B/2021/PN Psb. This study employed a normative legal method with statutory, scientific journal, and case approaches. The research data were derived from primary and secondary legal materials collected through library research and then analyzed qualitatively. The results show that the panel of judges based its decision on the fulfillment of all elements of the criminal act of aggravated theft as regulated under Article 363 paragraph (1) points 1 and 4 of the Criminal Code, by considering the facts of the trial, witness testimonies, the defendant’s confession, and evidence, so that the defendant was sentenced to seven months’ imprisonment. From the perspective of Islamic criminal law, the defendant’s act constitutes the jarimah sariqah, but because the conditions for the application of hudud were not fully met, the appropriate sanction is categorized as ta’zir. These findings contribute to strengthening comparative studies between positive criminal law and Islamic criminal law and show that the judge’s decision is in line with the principles of justice and the objectives of punishment in Islamic criminal law.